International Integrated Engineering Summit 2014 - Al Emran Ismail; Amir Khalid; Aziman Madun; Ahmad Kueh Beng Hong; Fariza Mohamad; Hamidon Salleh; Kamaruddin Ambak; Mohammad Kamil Abdullah; Mohd Azlis Sani Md Jalil; Mohd Ezree Abdullah; Mohd Fahrul Hassan; Mohd Halim Irwan Ibrahim; et al. (Trans Tech Publications Ltd, 2015)
Selected, peer reviewed papers from the 1st International Integrated Engineering Summit (IIES 2014), December 1-4, 2014, Batu Pahat, Malaysia